The right to vote and the possibility of participation in political and public life of adults under guardianship in international human rights treaties and legislation of Bosnia and Herzegovina - Miković Borjana; Škrbić Ajla (Anali Pravnog Fakulteta u Beogradu, 2020)
The right to vote, which is one of the universal human rights, is still not available to all citizens in Bosnia and Herzegovina. More specifically, adults under guardianship are being deprived of their legal capacity. This is a consequence of the inherited legal past and occurs despite the fact that it violates the Constitution of Bosnia and Herzegovina, as well as numerous international legal instruments ratified by BH. This practice allows persons with deprived legal capacity to be automatically deprived of their right to vote without any individual assessment and/or court decision. It is contrary to the European Court of Human Rights practice as well as to the Convention on the Rights of Persons with Disabilities, which prescribes that persons with disabilities enjoy legal capacity on an equal basis with others in all aspects of life, including the right and opportunity to vote and be elected.